2011
DOI: 10.1088/0960-1317/21/2/025007
|View full text |Cite
|
Sign up to set email alerts
|

Quality-factor amplification in piezoelectric MEMS resonators applying an all-electrical feedback loop

Abstract: An all-electrical velocity feedback control to enhance the quality factor of piezoelectric aluminium nitride (AlN)-based microcantilevers and microbridges was implemented. Two alternatives to obtain a velocity-proportional signal were demonstrated depending on the top electrode configuration. For a straightforward electrode design in one-port configuration (i.e. self-actuation and self-sensing), a velocity signal, proportional to the piezoelectric current, was used in the feedback loop by cancelling out the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…4 When operated in air or in liquid, the quality factors dramatically decrease, thus leading to loss of performance. Several strategies have been proposed to overcome those difficulties, such as active closed loop enhancement 4,5 or parametric amplification, introduced by the pioneering work of Rugar and Gr€ utter 6 and used for torsional microresonators. 7 More recently, this principle has been applied to micro and nano-beams driven by Lorentz forces 8 or by piezoelectric action, 9,10 to an array of microcantilevers 11 and to carbon nanotubes.…”
mentioning
confidence: 99%
“…4 When operated in air or in liquid, the quality factors dramatically decrease, thus leading to loss of performance. Several strategies have been proposed to overcome those difficulties, such as active closed loop enhancement 4,5 or parametric amplification, introduced by the pioneering work of Rugar and Gr€ utter 6 and used for torsional microresonators. 7 More recently, this principle has been applied to micro and nano-beams driven by Lorentz forces 8 or by piezoelectric action, 9,10 to an array of microcantilevers 11 and to carbon nanotubes.…”
mentioning
confidence: 99%
“…Most recently, an all-electrical feedback loop was presented in [6] which uses an I-V conversion of the piezoelectric current directly as feedback by adding it to the stimulus. This present study presents an alternative approach, shown in Fig.…”
Section: Description Of the Lock-in Driven Quality Factor Enhancementioning
confidence: 99%
“…4 applying a lock-in amplifier connected to the I-V converter. The lock-in working in X-Y mode extracts the real part, representing the conductance G of the piezoelectric aluminum nitride (AlN) actuated MEMS resonator replacing the original, low level, highly amplified and thus noisy feedback signal [6] and modulates the voltage amplitude applied to the MEMS resonator.…”
Section: Description Of the Lock-in Driven Quality Factor Enhancementioning
confidence: 99%
See 2 more Smart Citations